From manganese oxide to manganese sulphide: Synthesis and its effect on electrochemical energy storage performance - Almeida, M. M. (2022)
High power pseudocapacitors are extremely relevant to answer specific needs in the current energy transition arena and to implement an efficient renewable energy society. However, literature shows that are still open gaps concerning improvement of their energy density at high power, conversion efficiency, cost and cycle life. Electrodes based on active transition metal compounds, and in particular metal sulphides, evidence high potential to meet these objectives. This work discusses the dependence on the synthesis route of the charge storage mechanism of manganese sulphide-based materials and relates the pseudocapacitive response of these electrodes with their polycrystalline nature. Results reveal that a manganese oxy-sulphide mixture can achieve a high specific capacitance of 231 F.g−1 at 0.5 A/g in a 0.65 V active window. These values represent a 31.5 % increase compared to pure rambergite, γ-MnS, and 436 % compared to pure hausmannite Mn3O4 prepared under the same conditions. Moreover, the results show that manganese oxy-sulphide electrodes are characterized by good charge retention (73%), and superior long term capacity retention (above 86%) after 5000 cycles, evidencing potential for high power energy storage applications.